MINERALOGY OF CHROMITITES OF MOUNT POKLONNAYA OF THE KARABASH MASSIF, SOUTH URALS - V.I. Popova; E.V. Belogub; M.A. Rassomakhin; V.A. Popov; P.V. Khvorov (Минералогия)
Mineral composition of chromitites and host serpentinites from a quarry at Mt. Poklonnaya of the Karabash serpentinite massif is studied using optical and electron microscopy. In addition to previously known native osmium and laurite, eight minerals of platinum group elements (PGE) are found: isoferroplatinum, irarsite, iridium, naldrettite, cuproiridisite, sperrilite, tolovkite and erlichmannite. It is found that magnesioalumochromite is the early magmatic Cr-spinel and magnesiochromite and ferrichromite are late magmatic. The earliest native iridium and native osmium are replaced by PGE sulfides, arsenides and stibnides. Magnesiochromite is associated with native gold, Ni chalcohenides (gersdorffite, millerite, pentlandite, heaslewoodite) and chalcopyrite. The formation of Cr-magnetite, magnetite, native iron, native nickel, galena and barite is related to serpentinization. Carbonates (calcite and dolomite), brucite, andradite, sepiolite and an unidentified Ca-silicate formed at the latest stage of serpentinization. Secondary Ni minerals (gaspeite, nepuite, «garnierite») are most likely the products of the latest mineral-forming process.